2021
DOI: 10.3390/cancers13030416
|View full text |Cite
|
Sign up to set email alerts
|

C1q–HA Matrix Regulates the Local Synthesis of Hyaluronan in Malignant Pleural Mesothelioma by Modulating HAS3 Expression

Abstract: Increased hyaluronic acid (HA) production is often associated with cancer progression. In malignant pleural mesothelioma (MPM), HA is found at elevated levels in pleural effusions and sera of patients, and it has been widely debated whether MPM cells are able to produce HA by themselves or through the release of growth factors stimulating other cells. Another key component of the MPM microenvironment is C1q, which can act as a pro-tumorigenic factor favoring cell adhesion, migration and proliferation. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Kou et al [23] through GEO database and the research on Idiopathic Pulmonary Fibrosis (IPF) and non-small cell lung cancer, they found that the prognosis of non-small cell lung cancer and IPF patients with high levels of C1Q is poor. Vidergar et al [24] reported that C1Q promoted the growth of malignant pleural mesothelioma. Besides, in liver cancer, C1Q promoted migratory and invasive phenotypes [25] .…”
Section: Resultsmentioning
confidence: 99%
“…Kou et al [23] through GEO database and the research on Idiopathic Pulmonary Fibrosis (IPF) and non-small cell lung cancer, they found that the prognosis of non-small cell lung cancer and IPF patients with high levels of C1Q is poor. Vidergar et al [24] reported that C1Q promoted the growth of malignant pleural mesothelioma. Besides, in liver cancer, C1Q promoted migratory and invasive phenotypes [25] .…”
Section: Resultsmentioning
confidence: 99%
“…In gastric cancer cells, hyaluronan synthesis is also associated not only with local and nodal spread but also with reduced survival rates [44]. A marked increase of hyaluronan is also evident in malignant mesothelioma, where it promotes pro-tumourigenic activities [45,46]. Recently, it was also shown that hyaluronan remodels the microenvironment of mesenchymal colorectal tumours, promoting the appearance of a more heterogeneous epithelial environment that favours invasion through interaction with activated fibroblasts [47].…”
Section: Hyaluronan Metabolism Deregulation In Tumoursmentioning
confidence: 99%
“…Since HA-bound C1q is capable of modulating HAS expression (27), we aimed at determining whether C1q would impact also on HYAL expression, focusing on the main degradation enzymes, HYAL1 and HYAL2. Moreover, we investigated the involvement of gC1qR as a potential receptor involved in the process.…”
Section: Introductionmentioning
confidence: 99%